Negotiating local versus global needs in the International Long Term Ecological Research Network's socio-ecological research agenda - Holzer, J. M.; Adamescu, M. C.; Bonet-Garcia, F. J.; Diaz-Delgado, R.; Dick, J.; Grove, J. M.; Rozzi Marin, Ricardo Roberto; Orenstein, D. E. (My University, 2018)
Over the past decade, long-term socio-ecological research (LTSER) has been established to better integrate social science research and societal concerns into the goals and objectives of the International Long-Term Ecological Research (ILTER) network, an established global network of long-term ecological monitoring sites. The Horizon 2020 eLTER project, currently underway, includes as one of its key objectives to evaluate the performance of LTSER platforms. This article reflects part of this evaluation: six LTSER platforms were assessed through site visits of the lead author, coupled with reflections and insights of the platform managers, who are also co-authors. We provide background for the mission and goals of LTSER, then assess the six international LTSER platforms-Baltimore Ecosystem Study LTER, USA; Braila Island LTSER, Romania; Cairngorms LTSER, UK; Donana LTSER, Spain; Omora Ethnobotanical Park Cape Horn LTER, Chile; and Sierra Nevada LTSER, Spain. While based on a strong theoretical foundation in socio-ecological research, there has been a steep learning curve for scientists applying the concept in practice at LTSER platforms. We show positive impacts that have been achieved, including contributions to policy, land-use planning, and natural resource management. We explain key aspects of LTSER platforms that have proven challenging, including management, interdisciplinary integration, and stakeholder collaboration. We characterize the tensions between top-down desires for network harmonization, bottom-up demands such as local policy relevance, and platform-level constraints such as time and budget. Finally, we discuss challenges, such as local context dominating the character of LTSER platforms, and the fact that scientists are often disincentivized from engaging in transdisciplinary science. Overall, we conclude that while the international network offers important advantages to its members, a more productive balance between local and global goals could be achieved, and members may need to temper their expectations of what the network can and cannot offer at the local level.
Keywords: long-term ecological research; long-term socio-ecological research; transdisciplinary; network; sustainability; ilter; global research infrastructure